Finite Element Modelling of Rubber-Metal Vibration Isolators with Holes for the Vibration Protection System of Buildings - Vladimir L. Mondrus; Dmitry K. Sizov; Timofei M. Kvasnikov (Железобетонные конструкции)
The article presents a calculation of rubber-metal vibration isolators with five holes of different diameters using a software package that implements the finite element method. A comparative analysis of the Eigen frequencies of rubber-metal vibration isolators with five holes (one in the center, 4 symmetrically at the corners) and without holes is presented. Finite element models of a rubber-metal vibration isolator with and without holes are modeled, and their characteristics are analyzed. The results show that vibration isolators with several symmetrically located holes have several advantages in a number of parameters to vibration isolators without holes, and, therefore, can be used for vibration isolation of buildings, especially in the case of delayed installation of vibration protection.